Effects of caged stress on the duodenal tissue structure, antioxidant capacity and gene mRNA expression level of Shaoxing duck - GU Tiantian; TIAN Yong; ZHOU Wei; LIU Guofa; CHEN Li; ZENG Tao; WU Xinsheng; XU Qi; CHEN Guohong; LU Lizhi (浙江大学学报. 农业与生命科学版, 2020)
Eighty 200-day-old Shaoxing ducks were randomly divided into two groups, including the ground group (control group) and the caged stress group (treatment group). Then the tissue damage degree of the duodenum and antioxidant indicators were determinated, and the relative expression levels of endoplasmic reticulum stress gene, inflammation-related gene and apoptotic gene mRNA were detected by real-time fluorescence polymerase chain reaction (RT-PCR) at 1, 2, 4, 7 and 10 d after cage rearing, which providing theoretical basis for the large-scale breeding of laying ducks and the scientific prevention for caged stress disease. The results showed that: 1) With the increase of caged stress time, the damage degree of the duodenum in the treatment group gradually increased, mainly manifested by inflammatory cell infiltration and intestinal gland epithelial cell shedding. 2) During the progress of caged stress, the duodenal malondialdehyde (MDA) content, total antioxidant capacity (T-AOC), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), activities in the treatment group showed fluctuating changes, while the catalase (CAT) activity increased significantly at the 7th day after cage rearing (P＜0.05). 3) RT-PCR results showed that compared with the control group, the endoplasmic reticulum stress-related genes glucose regulated protein 78 (GRP78) and CCAAT/enhancer-binding protein-homologous protein (CHOP) mRNA expression levels showed fluctuating changes, and increased significantly in the Shaoxing ducks at the 2nd and 10th day after cage rearing (P＜0.05). In addition, the expression level of apoptosis-related gene Bcl-2 associated X protein (Bax) mRNA increased significantly at the 7th and 10th day after cage rearing (P＜0.05), while the expression of cysteinecontaining aspartate-specific proteases-3 (Caspase3) mRNA expression level was not significantly different from the control group (P＞0.05). At the same time, the cyclooxygenase-2 (COX-2) mRNA expression level was significantly up-regulated and increased significantly at the 10th day after cage rearing (P＜0.05), while the expression level of inducible nitric oxide (iNOS) showed a trend of decreasing first and then increasing. The above results indicate that the stress of caged rearing causes different degrees of tissue damage on Shaoxing duck duodenum, which enhances the body’s antioxidant capacity. At the same time, the up-regulation of endoplasmic reticulum stress intensity eventually leads to apoptosis and inflammation.